Chronic enteropathy in dogs – retrospective case analysis and results of an owner survey - Treese, Julia S.; Nolte, Ingo; Bach, Jan-Peter (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2021)
Objective Chronic gastrointestinal diseases in dogs are common and often require intensive diagnostic work-up and lifelong therapy. In this study, a survey of owners of affected dogs was conducted in parallel with a retrospective case analysis from the clinic’s documentation system.Material and methods The records of dogs with gastrointestinal symptomatology and exclusion of an extraintestinal cause, presented from January 2011 to October 2018, were acquired from the clinic’s case system and analysed. Patient owners were interviewed using a questionnaire regarding diagnosis, treatment, course of the disease and improvement in the dog’s quality of life as a result of treatment. To gain a better understanding of influencing factors for the different subtypes of chronic enteropathy, differentiation was made into feed-responsive (FRE), antibiotic-responsive (ARE), immunosuppressant-responsive (IRE), and nonresponsive enteropathy (NRE) according to the success of different therapeutic approaches.Results Of 125 patient owners contacted, 81 participated in the study. The majority of the 81 dogs had FRE (45; 55.6 %), 11 (13.6 %) dogs had ARE, 23 (28.4 %) had IRE and 2 (2.5 %) had NRE. At the disease onset, dogs in the FRE and ARE groups were significantly younger than those in the IRE group. Interviews with dog owners showed that veterinary recommendations had not been consistently implemented, particularly in dogs in the FRE group. Successful treatment resulted in significant improvement in the quality of life in patients in all 3 groups according to owner assessment, with no differences between the groups.Conclusion and clinical relevance The majority of the contacted dog owners agreed to participate in the survey. A retrospective case analysis in combination with an owner survey is helpful to elicit the owners’ assessment of their dog’s treatment and disease course and to reveal starting points for improved owner compliance.
Keywords: Chronic gastrointestinal diseases; retrospective work-up; data acquisition